Pengaruh Kompres Jahe Terhadap Penurunan Intensitas Nyeri Pada Penderita Gout Arthritis Di Upt Puskesmas Helvetia Medan Tahun 2024 - Faswita, Wirda; Elfira, Eqlima (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Gout Arthritis is an inflammatory arthritis disease caused by the accumulation of crystalline acid which is the result of the breakdown of purines. The most common symptom experienced is that the patient feels pain in the joint. Nonpharmacological therapies to relieve joint pain include the use of red ginger compresses containing gingerol, shogaol, and zingeron. The results of the initial survey at the Helvetia Health Center from May to July 2024 were obtained by 172 patients with Gout Arthritis. The type of research used is a type of quasi-experimental research with a pre-test post-test one-group research design. The sampling technique in this study uses the Purposive Sampling Technique, namely 26 people with Gout Arthritis who visited the Helvetia Medan Health Center. Data collection using Pain Level Measurement Sheets and SOPs. This study revealed that the change in pain level in patients with Gout Arthritis in the ginger compress intervention group, with a total of 26 people (100%), showed an average score of 5.58, a rating of 2.31, and an Asymp Sig. (2-tailed) result of 0.000. This shows that the administration of ginger compresses has an effect on reducing pain intensity in patients with Gout Arthritis. The results of this study are expected to be used as an illustration to improve health promotion in reducing pain intensity in patients with Gout Arthritis